Responsible environmental behavior and attitude in university students in Lima, Peru - Olivera Carhuaz, Edith (2020)
Attitude towards the environment is an indicator of environmental behavior and is manifested in the action and pro-environmental regulations. The purpose of this study was to know the relationship between behavior and responsible environmental attitude in university students in Lima, Peru. The approach was quantitative, with a descriptive-correlational design, and the sample consisted of 287 male and female students from different careers. The instruments used were two scales that measure the environmental attitude: perception of environmental problems, perception of reasons for environmental problems; intention of pro-environmental behaviors and, types of environmental concerns; the same ones that independently evaluate the attitude and proambiental behavior. The positive relationship between responsible environmental behavior and attitude was determined, as well as between the component factors of the variables.